Investigating Language Team Interventions and Arabic Proficiency among Female Students: An Islamic Boarding School Case Study: Penelusuran Inisiatif Tim Bahasa terhadap Profisiensi Bahasa Arab: Studi Kasus pada Siswa Perempuan di Sekolah Boarding Islam - Silmi, Siti Adina; Anwar, Najih (Indonesian Journal of Education Methods Development, 2023)
This study investigates the influence of a language team's efforts on Maharah Kalam proficiency among female students at Al Fattah Buduran Islamic Boarding School in Indonesia. Employing a quantitative correlational approach, the research analyzes data using hypothesis and correlation testing via SPSS Windows 26. The results indicate a non-significant relationship (p = 0.120 > 0.05) between the language team intervention and Maharah Kalam proficiency, suggesting that the null hypothesis (Ho) is accepted. The observed negative correlation of 0.023 (2.3%) implies a minimal adverse effect. Thus, this study concludes that the Language Team variable holds no significant sway over the Maharah Kalam variable among female students at the boarding school, emphasizing the complex interplay of factors affecting Arabic language acquisition. Highlights: Limited Impact: The study reveals that the language team's initiatives did not significantly influence Arabic language proficiency among female students. Correlation Analysis: Quantitative analysis using SPSS 26 showed a non-significant negative correlation (2.3%) between the language team efforts and Maharah Kalam proficiency. Complex Language Acquisition: The findings underscore the intricate nature of Arabic language acquisition, indicating the need for comprehensive approaches beyond specific interventions. Keywords: Arabic proficiency, language team, Islamic boarding school, Maharah Kalam, Maharah Kalam, language acquisition.